Diversification and biogeography of Rhacophoridae – a model testing approach - Ellepola, Gajaba; Meegaskumbura, Madhava (Frontiers in Ecology and Evolution, 2023)
A central focus of evolutionary biology is to understand species diversity by studying how they arrived at their current geographic distributions. The biogeography of the Old World tree frogs in the family Rhacophoridae has been extensively studied suggesting an early Paleogene origin in Asia (out of Asia hypothesis) with alternative hypotheses in play. However, these alternative hypotheses especially considering adjacency of biogeographical regions and plate tectonics have not been tested empirically. Here using a comprehensive time calibrated phylogeny and constrained dispersal multipliers we studied the biogeographical history and diversification of Rhacophoridae, distributed in five biogeographical regions. Five hypotheses suggesting different centers of origin, and additional hypotheses considering adjacency and plate tectonics were tested to delineate the biogeographical history of Rhacophoridae. In addition, various diversification models that accounted for factors such as lineage isolation time, diversity-dependence, paleotemperatures, speciation and extinction rates were also used to test patterns of diversification. Results confirmed an East/Southeast Asian center of origin (out of Asia), with dispersal likely mediated by plate tectonics and adjacency of biogeographical regions, which could be linked to periodic sea level fluctuations and climate changes. The best-fitting diversification models explained diversification through lineage isolation time and paleotemperature regimes, while diversity-dependent models had low support. Speciation was linearly dependent on time and paleotemperatures, while extinction rates were exponentially dependent on time and linearly dependent on paleotemperature. Our findings demonstrate that variable extinction rates contribute towards maintaining a constant diversification rate for rhacophorids. We discuss that episodic major extinction events on the Indian Plate may have played a major role in shaping the early evolution of Rhacophoridae thus favoring an Out of Asia hypothesis in the empirical models. However, current biogeographic models may not be sufficient to explain the origin of Rhacophoridae, as multiple factors are likely at play.